STOR(Y)ING DESMADRE ON THE INTERNET: THE POLITICS, AFFECT AND ETHICS OF ONLINE QUEER LATIN AMERICAN CABARET ARCHIVES - GUZMAN, CARINA (AoIR Selected Papers of Internet Research, 2020)
In this paper I discuss my doctoral research-creation project: the design of an online archive of the community materials of a Mexico City-based queer cabaret collective active between 2006-2012, called Burlesquimeras, which I was a member of. While digital photographs and social media certainly existed in the years Burlesquimeras was active, it was before the two were seamlessly integrated (at least in the Mexican context) through the ubiquity of smartphones and unlimited data. That is, an online search of Burlesquimeras does not yield a significant collection of photographs that can be potentially culled or scrapped from social media. Most of the digital photographs and other ephemera, have been stored by its members in the mess or clutter of the homes and hard drives of the community members. Moreover, I explain a concept I coined: “stor(y)ing”. It is influenced by theoretical structures and praxes that challenge and expand notions of evidence, sources and the possibilities of historic narratives, such as Hartman’s Critical Fabulation (2008, 2019), Cowan’s Cabaret Methods (Forthcoming) and Navarrete Linares’ use of Mesoamerican myth and cosmohistoria (2011, 2018). I propose that the very act of caring for these materials by their queer creators, albeit in a messy way, and precisely because it is in a messy way, is already an act of story-telling. I refer to this practice as stor(y)ing: a storage of materials that itself articulates a story.